An Ultrahigh Rate and Stable Zinc Anode by Facet‐Matching‐Induced Dendrite Regulation. Issue 37 (12th August 2022) - Yi, Zhehan; Liu, Jiaxin; Tan, Shandong; Sang, Zhiyuan; Mao, Jing; Yin, Lichang; Liu, Xiaoguang; Wang, Liqun; Hou, Feng; Dou, Shi Xue; Cheng, Hui‐Ming; Liang, Ji
Abstract: Resource‐abundant metal (e.g., zinc) batteries feature intrinsic advantages of safety and sustainability. Their practical feasibility, however, is impeded by the poor reversibility of metal anodes, typically caused by the uncontrollable dendrite enlargement. Significant effort is exerted to completely prevent dendrites from forming, but this seems less effective at high current densities. Herein, this work presents an alternative dendrite regulation strategy of forming tiny, homogeneously distributed, and identical zinc dendrites by facet matching, which effectively avoids undesirable dendrite enlargement. Confirmed by multiscale theoretical screening and characterization, the regularly exposed Cu(111) facets at the ridges of a copper nanowire are capable of such dendrite regulation by forming a low‐mismatched Zn(002)/Cu(111) interface. Consequently, reversible zinc electroplating/stripping is achieved at an unprecedentedly high rate of 100 mA cm −2 for over 30 000 cycles, corresponding to an accumulative areal capacity up to 30 Ah cm −2 . A full cell using this anode shows a high capacity of 308.3 mAh g −1 and a high capacity retention of 91.4% after 800 cycles. This strategy is also viable for magnesium and aluminum anodes, thus opening up a promising and universal avenue toward long‐life and high‐rate metal anodes. Abstract : The strategy of dendrite regulation,  growing tiny, identical, and homogeneously distributed Zn dendrites by facet matching of Cu(111)/Zn(002),  can achieve reversible Zn plating/stripping and long‐life Zn anode at ultrahigh current densities.